MANAJEMEN LABA DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA PADA PERUSAHAAN MANUFAKTUR DI BEI - Felicia Benedicta; Ricky A. Mulyana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence the influence of leverage, tax planning, firm size, audit committee, independent commissioner, sales growth, and auditor independence on earning management.The population of this research are manufacturing companies listed in Indonesia Stock Exchange from 2018 to 2020. The sample in this research obtained by using the purposive sampling method that were 62 companies that met the sampling criteria. The hyphotesis test used of this is multiple regression method. The measurement of earning management of this research uses Modified Jones model to estimate the value of discretionary accruals as the proxy of earnings management. The result show that leverage,tax planning, and sales growth have influence to earnings management, while firm size,audit committee, independent commissioner, and auditor independence have no influence to earnings management.